PENGARUH TERAPI BERMAIN TERHADAP INTERAKSI SOSIAL ANAK AUTIS DI SDLB PROF. DR. SRI SOEDEWI MASJCHUN SOFWAN, SH JAMBI TAHUN 2014 - Suryati Suryati; Rahmawati Rahmawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Indonesia in 2004 an estimated 475,000 people and now every one of the 150 children born autism. Impaired social interaction is often found in people with autism and is a typical symptom of autism. This study is a quantitative research design (pre-experimental designs), to form one group pretest-posttest design. This study aims to determine the effect of Play Therapy on Children Autism Social Interaction. The population is all people with autism in SLB Prof. Dr. Sri Soedewi Masjchun Sofwan, SH Jambi were 17 childrens who grade 1-3 (age 6-8 years). This study was conducted in July 2014, data was collected by observation. Then analyzed using univariate and bivariate analysis. Bivariate analysis using t-test. The results of the statistical test p-value 0:00 obtained it can be concluded there effect Play Therapy on Social Interaction Autistic Children in SLB Prof. Dr. Sri Soedewi Masjchun Sofwan, SH Jambi in 2014. Expected SDLB may consider the use of play therapy as an adjunctive therapy for people with autism.Keyword: terapi bermain, interaksi sosial, autisme